Kebijakan Sosial Di Perkotaan Sebagai Sebuah Kajian Implementatif - Ni Luh Putu Ening Permini (Jurnal Ilmiah Cakrawarti, 2018)
Human being cannot separate by a social problem. There is social problem on rural and urban area. But, more problems arise in urban than rural area. Base of it, the Urban Management have implementing as a management process to make an ideal city system as like as something was expected. The focus of urban management is closely connecting with the needs of the physical aspects, social and economic aspect of communities. The pattern of its management is highly related to the level of complexity of urban problems which related to a number of factors and challenges, such as population, high level on urbanization, Poverty increasing/minimally of employment opportunities, increasing of social inequality/economic inequality, declining of environmental quality in urban area, and ability human resources lim- itation, institutionally and fundrising for develop and to maintain the urban infrastructure. So- cial policy basically is a combination of two activities, discovering) and finding a solution for social problem (Bessant, et al 2009:3). In this case, integrated social policies in the academic scientific activities such as research using to find social issue such as poverty, that research will using to policy formulating. But sometime, government showed opposite. That was a break- through made with the means to anticipated a number of potential act which any time become to threaten. It includes several stages, as like as movement, awareness of unity among them, make an organization, tightened them line, all of that using to fight against an intervention of the officer. There are two Factors that influence to the existence of street vendors in the city of Denpasar. First aspects including problem through regulation, facilities and infrastructure, also human resources management. Another aspects is socio-cultural and economical factors